Pengaruh Sikap Disiplin Belajar terhadap Peningkatan Hasil Belajar Aqidah Akhlak Siswa MI Al-Hijrah Bontang Tahun Pembelajaran 2022/2023 - Erlinda, Eka Julita; Ihsan, Muh (NABAWI: Jurnal Penelitian Pendidikan Islam, 2024)
Student learning outcomes in the subject of Aqidah Akhlak still vary, especially in MI Al Hijrah Bontang there are satisfactory, moderate, and unsatisfactory. So, especially in the subject of learning aqidah akhlak is not good because students do not listen to the learning given by the teacher. The purpose of this study was to determine the effect of learning discipline on improving the Aqidah Akhlak learning outcomes of MI Al Hijrah Bontang students, in addition to knowing whether a disciplined attitude can improve Aqidah Akhlak learning outcomes. The method used by researchers is quantitative. Data sources were obtained from interviews with the Vice Principal and Aqidah Akhlak Teacher. Observations were made according to data requirements, in addition to these two sources the researcher also distributed questionnaires to students as respondents as many as 51. The results of the data from the respondents were analyzed using a simple correlation coefficient analysis. After the test will show the results of the study. The results showed that the Learning Discipline Attitude had a significant effect on the Improvement of Aqdiah Akhlak Learning Outcomes. this is evidenced by the value of tcount> ttabel, then the test decision is the r value of the significant correlation analysis results, the H0 analysis is rejected and Ha is accepted. Based on the calculation of tcount> ttable or 4.565> 2.007, then Ha is accepted. The conclusion shows that there is an influence of the attitude of learning discipline on improving the learning outcomes of aqidah akhlak in MI Al Hijrah Bontang students.